TRANSLATING MOCHTAR LUBIS’S SHORT STORY “KULI KONTRAK” INTO ENGLISH: A NOVICE TRANSLATOR’S AUTOETHNOGRAPHY - Dewi, Novita (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2021)
This article is of reflection category exploring the common mistakes often occur in translating Indonesian literary texts into English by a non-native speaker of English. It argues that translation of literary texts is meticulous as it should involve interpretation and fluency in both source and target languages as well as creativity in order that the translated texts communicate equally well. It is the communicative power of translation that makes this undertaking of language transfer miraculous. Applying sufficient principles in translation and creative writing method, this article exemplifies the translation process of Mochtar Lubis’s short story “Kuli Kontrak” into “The Contract Coolies” that appears in the Your Story page of California-based Dalang Publishing bi-lingual website. Autoethnography is the method used in reporting the results. Three main problems that ensue in the Indonesian-English translation of this short story include (1) the concept of time, (2) the non-idiomatic use of body-parts, and (3) the unnecessary use of object construction/ passive voice that often do not translate well in English. By tackling these problems, the English reader may hopefully obtain the meaning-message of the short story as closely as possible to that acquired by Indonesian readers.